The cost effectiveness of Erenumab in migraine therapy: A systematic review - Alshayban, Dhafer (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Migraine is a common neurological condition that affects millions of people worldwide. Newly approved treatments for the prevention of migraine including calcitonin gene-related peptide monoclonal antibodies such Erenumab, might help in case of the failure of other medications. Therefore, it was decided to conduct a systematic literature review of cost effectiveness of Erenumab which is the first and most common medication among its group. Methods: Pharmacoecnomics studies which were written in English and published between 2015 and 2025 were included. Several databases such as Scopus, Web of Science, OVID Medline, Embase, PubMed, and Dimensions were searched independently. Results: Six published studies, and 2 reports were selected from an initial pool of 974 based on predefined inclusion criteria. They were conducted across different countries settings including the United States, United Kingdom, Sweeden and Greece and, Spain. These studies adapted decision-analytic models, using either standalone Markov models or decision trees in combination with Markov models, adapted with country-specific data to evaluate the cost effectiveness of Erenumab. Conclusions: Erenumab’s cost-effectiveness is context-dependent, varying according to local drug pricing, healthcare system structures, and patient populations. Evidence suggests that Erenumab is a cost-effective option for individuals with chronic or episodic migraine who have not responded to previous treatments. However, it was not cost effectiveness in countries such as Iran and Greece unless a significant discount in price was applied. Future research should prioritize pharmacoeconomics evaluations comparing Erenumab with newer agents, such as fremanezumab and galcanezumab, to support more informed policy and reimbursement decisions.